IMPROVE STUDENT LEARNING OUTCOMES USING STUDENT WORKSHEETS BASED ON THE APOS MODEL ASSISTED BY GEOGEBRA - Lilia Gina Febrila; Hanifah Hanifah; Hari Sumardi; Tria Utari (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The observation results showed that practicum activities and student learning outcomes in algebra courses were not optimal. Therefore, a learning model is needed that can make students carry out practical activities directly in class and can improve student learning outcomes This study aimed to determine the increase in student learning outcomes through the use of Rational Function Student Worksheets based on the GeoGebra-assisted APOS model. The type of research carried out is Classroom Action Research (CAR). The research instrument was in the form of a learning achievement test sheet. The subjects of this study were first semester students of the Mathematics Education Study Program at Bengkulu University in 2022. The results showed that the average learning outcomes were 71.26 in cycle I and 82.05 in cycle II with a percentage of completeness in student learning outcomes of 82.05%. in cycle II. So it can be concluded that learning using rational function student worksheets based on the APOS model assisted by GeoGebra can improve student learning outcomes.Hasil observasi menunjukkan bahwa kegiatan praktikum dan hasil belajar mahasiswa pada mata kuliah aljabar belum optimal. Oleh karena itu, diperlukan model pembelajaran yang dapat membuat mahasiswa melakukan kegiatan praktikum secara langsung dikelas dan dapat meningkatkan hasil belajar mahasiswa. Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar mahasiswa melalui penggunaan Lembar Kerja Mahasiswa fungsi rasional berbasis model APOS berbantuan GeoGebra. Jenis penelitian yang dilaksanakan adalah Penelitian Tindakan Kelas (PTK). Instrumen penelitian berupa lembar tes hasil belajar. Subjek penelitian ini yaitu mahasiswa semester I Program Studi Pendidikan Matematika Universitas Bengkulu Tahun 2022. Hasil penelitian menunjukan bahwa rata-rata hasil belajar yaitu 71,26 pada siklus I dan 82,05 pada siklus II dengan persentase ketuntasan hasil belajar mahasiswa sebesar 82,05% pada siklus II. Sehingga dapat disimpulkan bahwa pembelajaran menggunakan lembar aktivitas mahasiswa fungsi rasional berbasis model APOS berbantuan GeoGebra dapat meningkatkan hasil belajar mahasiswa.